Aptamer decorated hyaluronan/chitosan nanoparticles for targeted delivery of 5-fluorouracil to MUC1 overexpressing adenocarcinomas. (5th May 2015) - Ghasemi, Zahra; Dinarvand, Rassoul; Mottaghitalab, Fatemeh; Esfandyari-Manesh, Mehdi; Sayari, Elmira; Atyabi, Fatemeh
Highlights: Here we report hyaluronic acid/chitosan nanoparticles as 5-fluorouracil drug carrier. Nanoparticles showed suitable size, PDI, stability and sustained drug release. Both targeted and non-targeted nanoparticles were more cytotoxic than free drug. Cellular studies demonstrated higher toxicity and uptake in MUC1 + cells for targeted nanoparticles. Abstract: An aptamer (Apt) conjugated hyaluronan/chitosan nanoparticles (HACSNPs) were prepared as carrier for targeted delivery of 5-fluorouracil (5FU) to mucin1 (MUC1) overexpressing colorectal adenocarcinomas. Nanoparticles had about 181 nm size, encapsulation efficiency of 45.5 ± 2.8 and acceptable stability. Conjugation of MUC1-binding Apt to the surface of the nanoparticles was confirmed by gel electrophoresis. Toxicity and cellular uptake of nanoparticles were investigated by in vitro cytotoxicity assays and confocal scanning microscopy in (MUC1 + ) human adenocarcinoma and (MUC1 − ) Chinese hamster ovary cells. Toxicity of nanoparticles were significantly higher in comparison with free drug in both cell lines while this rising was more efficient for nanoparticles decorated with Apt in MUC1 + cell line. The same result was observed in the cellular uptake study. It could be concluded that the present system has the potential to be considered in treatment of MUC1 + colorectal adenocarcinomas.